Epigenetics of Bladder Cancer: Where Biomarkers and Therapeutic Targets Meet - Martinez, Victor G.; Munera-Maravilla, Ester; Bernardini, Alejandra; Rubio, Carolina; Suarez-Cabrera, Cristian; Segovia, Cristina; Lodewijk, Iris; Dueñas, Marta; Martínez-Fernández, Mónica; Paramio, Jesus Maria (Frontiers in Genetics, 2019)
Bladder cancer (BC) is the most common neoplasia of the urothelial tract. Due to its high incidence, prevalence, recurrence and mortality, it remains an unsolved clinical and social problem. The treatment of BC is challenging and, although immunotherapies have revealed potential benefit in a percentage of patients, it remains mostly as an incurable disease it is advanced state. Epigenetic alterations, including aberrant DNA methylation, altered chromatin remodeling and deregulated expression of non-coding RNAs are common events in BC and can be driver events in BC pathogenesis. Accordingly, these epigenetic alterations are now being used as potential biomarkers for these disorders and are being envisioned as potential therapeutic targets for the future management of BC. In this review, we summarize the recent findings in these emerging and exciting new aspects paving the way for future clinical treatment of this disease.